On the numerical solution of linear stiff IVPs by modified homotopy perturbation method - Chowdhury, Md. Sazzad Hossien; Hashim, Ishak; Rahman, Md. Mahmudur (2011)
In this paper, we introduce a method to solve linear sti® IVPs. The sug-gested method, which we call modi¯ed homotopy perturbation method, can be considered as an extension of the homotopy perturbation method (HPM) which is very efficient in solving a varety of di®erential and algebraic equations. In this work, a class of linear stiff initial value problems (IVPs) are solved by the classical homotopy per-turbation method (HPM), modified homotopy perturbation method and an explicit Runge-Kutta-type method (RK). Numerical comparisons demonstrate the limitations of HPM and promising capability of the MHPM for solving stiff IVPs. The results prove that the modified HPM is a powerful tool for the solution of linear stiff IVPs.